Research methods a tool for life - Beins, Bernard (Cambridge, UK New York, NY Cambridge University Press, 2017)
"Research Methods is an introduction to the importance of scientific research in everyday life and uses familiar examples to keep students engaged. The text analyzes controversies in psychology to stimulate student interest while explaining crucial methodological concepts. It presents ethical issues related to research, as well as social and cultural factors that might affect it, and provides a comprehensive introduction to a wide variety of methodologies. Through this book, students will learn how to generate research questions and select appropriate methodology, as well as to write a successful research report"-- Provided by publisher.
Psychology science and life -- Ethics in research -- Planning research, generating a research question -- Practical issues in planning your research -- Measurement and sampling -- Conducting an experiment : general principles -- Experiments with one independent variable -- Experiments with multiple independent variables -- Expanding on experimental designs, repeated measures and quasi-experiments -- Principles of survey research -- Correlational research -- Studying patterns in the natural world, observational approaches -- Research in depth, longitudinal and single-case studies -- People are different, considering culture and individual differences in research.
Keywords: Psychology -- Research -- Methodology